Problematic Use of Mobile Phones in Australia…Is It Getting Worse? - Oviedo-Trespalacios, Oscar; Nandavar, Sonali; Newton, James David Albert; Demant, Daniel; Phillips, James G. (Frontiers in Psychiatry, 2019)
Rapid technological innovations over the past few years have led to dramatic changes in today’s mobile phone technology. While such changes can improve the quality of life of its users, problematic mobile phone use can result in its users experiencing a range of negative outcomes such as anxiety or, in some cases, engagement in unsafe behaviours with serious health and safety implications such as mobile phone distracted driving. The aims of the present study are two-fold. First, this study investigated the current problem mobile phone use in Australia and its potential implications for road safety. Second, based on the changing nature and pervasiveness of mobile phones in Australian society, this study compared data from 2005 with data collected in 2018 to identify trends in problem mobile phone use in Australia. As predicted, the results demonstrated that problem mobile phone use in Australia increased from the first data collected in 2005. In addition, meaningful differences were found between gender and age groups in this study, with females and users in the 18-25-year-old age group showing higher mean Mobile Phone Problem Use Scale (MPPUS) scores. Additionally, problem mobile phone use was linked with mobile phone use while driving. Specifically, participants who reported high levels of problem mobile phone use, also reported handheld and hands-free mobile phone use while driving.